Pelatihan Dasar Pengelolaan Data Penelitian Kualitiatif “ Dari Transkrip Hingga Temuan” untuk Mahasiswa Di Pendidikan Sejarah Universitas Jambi - Adi Saputra, Muhamad; Mustofa Meihan, Andre; Wahyuni, Anny; Mareta, Yoan; Robbi Kurniawanti, Merci (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
Qualitative research is a widely used approach in historical studies; however, technical skills such as transcription, coding, and thematic analysis are often insufficiently mastered by undergraduate students. This community engagement program aimed to strengthen the research capacity of students in the History Education Study Program, FKIP Universitas Jambi, through a structured one-day training. The training covered four main sessions: an introduction to qualitative research, transcription practice, manual coding techniques, and writing initial findings. The training method was participatory and practical, emphasizing hands-on learning. The results showed a significant improvement in students’ understanding and skills, particularly in managing field data into systematic findings. Participant feedback indicated that the training was highly relevant and should be developed into a continuous program. This activity contributes to fostering a research-oriented academic culture and equips students with essential methodological competencies for qualitative, history-based research